Smooth muscle relaxant activity of Crocus sativus (saffron) and its constituents: possible mechanisms - Amin Mokhtari-Zaer; Mohammad Reza Khazdair; Mohammad Hossein Boskabady (Mashhad University of Medical Sciences, 2015)
Saffron, Crocus sativus L. (C. sativus) is rich in carotenoids and used in traditional medicine for treatment of various conditions such as coughs, stomach disorders, amenorrhea, asthma and cardiovascular disorders. These therapeutic effects of the plant are suggested to be due to its relaxant effect on smooth muscles. The effect of C. sativus and its constituents on different smooth muscles and the underlying mechanisms have been studied. Several studies have shown the relaxant effects of C. sativus and its constituents including safranal, crocin, crocetin and kaempferol on blood vessels. In addition, it was reported that saffron stigma lowers systolic blood pressure. The present review highlights the relaxant effects of C. sativus and its constituents on various smooth muscles. The possible mechanisms of this relaxing effect including activation of ß2-adrenoceptors, inhibition of histamine H1 and muscarinic receptors and calcium channels and modulation of nitric oxide (NO) are also reviewed.